Existence of Positive Solutions for a Nonlinear Second Order Periodic Boundary Value Problem (Journal of Nonlinear Modeling and Analysis, 2024)
By using the first eigenvalue corresponding to the relevant linear operator and the topological degree theorem, sufficient conditions for the existence of positive solutions for a nonlinear second order periodic boundary value problem are given. Our results improve and generalize some preliminary works.